A rare case of agenesis of dorsal pancreas - Devi D Jansirani; S Shiva deep; S Deepak Barathi (Wolters Kluwer Medknow Publications, 2012)
Agenesis of dorsal bud of the pancreas is an extremely rare congenital anomaly which results in absence of neck, body and tail of the adult pancreas. It may be associated with number of clinical features like diabetes mellitus, abdominal pain and chronic pancreatitis. Because of its rarity, we are reporting a case of agenesis of dorsal pancreas associated with early onset diabetes. Ultrasonography and Computed tomography showed absence of neck, body and tail of pancreas anterior to splenic vein and portal confluence; however head and uncinate process were normally present. Patient was thus diagnosed as agenesis of dorsal bud of pancreas.